Tissue Engineering Cartilage with Deep Zone Cytoarchitecture by High‐Resolution Acoustic Cell Patterning. Issue 24 (19th July 2022) - Armstrong, James P. K.; Pchelintseva, Ekaterina; Treumuth, Sirli; Campanella, Cristiana; Meinert, Christoph; Klein, Travis J.; Hutmacher, Dietmar W.; Drinkwater, Bruce W.; Stevens, Molly M.
Abstract: The ultimate objective of tissue engineering is to fabricate artificial living constructs with a structural organization and function that faithfully resembles their native tissue counterparts. For example, the deep zone of articular cartilage possesses a distinctive anisotropic architecture with chondrocytes organized in aligned arrays ≈1–2 cells wide, features that are oriented parallel to surrounding extracellular matrix fibers and orthogonal to the underlying subchondral bone. Although there are major advances in fabricating custom tissue architectures, it remains a significant technical challenge to precisely recreate such fine cellular features in vitro. Here, it is shown that ultrasound standing waves can be used to remotely organize living chondrocytes into high‐resolution anisotropic arrays, distributed throughout the full volume of agarose hydrogels. It is demonstrated that this cytoarchitecture is maintained throughout a five‐week course of in vitro tissue engineering, producing hyaline cartilage with cellular and extracellular matrix organization analogous to the deep zone of native articular cartilage. It is anticipated that this acoustic cell patterning method will provide unprecedented opportunities to interrogate in vitro the contribution of chondrocyte organization to the development of aligned extracellular matrix fibers, and ultimately, the design of new mechanically anisotropic tissue grafts for articular cartilage regeneration. Abstract : Engineering tissues with spatially organized cell features is essential for producing insightful biological models and effective clinical grafts. In this study, ultrasound standing waves are used to rapidly generate high‐resolution arrays of chondrocytes, which are immobilized throughout the volume of an agarose hydrogel and used to engineer hyaline cartilage with a cytoarchitecture analogous to the deep zone of articular cartilage.